Compatibility in vitro and effect of mixtures of three insecticides in the viability of Beauveria bassiana - MARÍN-M, PATRICIA; BUSTILLO P., ALEX E.; RIVERA-M., ARMANDO (Revista Colombiana de Entomología, 2000)
An experiment was conducted to evaluate the compatibility in vitro of a mixture of Beauveria bassiana (Balsamo) Vuillemin used in the control of coffee berry borer, ffypothenemus hampei, and three insecticides incorporated in a fungus growth media and mixed in an aqueous suspension simulating a spray tank. A combination of factors were created using three different sources of B. bassiana: isolates Bb9205 and Bb9002 produced on rice substrate, and a commercial product Brocartl". and three insecticides (diazinon in three formulations: Wetable Powder (WP), Wetable Emulsion (WE) and Encapsulated Suspension (ES); isazofos and metacrifos). Ali the insecticides were tested in the mixture using the commercial dosage (CD), half of the commercial dosage (1/i CD), and one-fourth of the commercial dosage WCD). Evaluations were made measuring the rate of fungus radial growth of the colony and the effect of the insecticides on fungus germination. It was found that diazinon WP and metacrifos had a heavy colony growth inhibition for isolate Bb9205 and Brocaril". Isazofos caused the lowest inhibition on Bb9205 accounting for a reduction of fungal growth in the media from 19.1% at the commercial rate to 11.7% when 11. CD was used. Diazinon ES in mixture with Brocaril® caused a reduction in growth from 17% at CD to 6.8% at v. CD. Total inhibition of germination of B. bassiana Bb9205 and Bb9002 was achieved when using diazinon WE at CD when mixed in an aqueous suspension for a period of up to 6 h; however, diazinon ES did not cause inhibition which may be attributed to the solvents used in the formulations. Diazinon WP and metacrifos had the same inhibitory effect on germination as showed when the radial growth was measured. Isolate Bb9002 was more sensible to the insecticides, this finding demonstrates that there are differences among isolates of the same fungus, which poses the necessity of selecting isolates more resistance to pesticides in IPM programs. In the experiment on conidia germination of Bb9205 reactivated in H. hampei using mixtures times for 1, 3, 6, 12 and 24 h with diazinon WE and isazofos, no significant differences were found compared to the control